2014
DOI: 10.3748/wjg.v20.i9.2279
|View full text |Cite
|
Sign up to set email alerts
|

Role of abnormal lipid metabolism in development, progression, diagnosis and therapy of pancreatic cancer

Abstract: There is growing evidence that metabolic alterations play an important role in cancer development and progression. The metabolism of cancer cells is reprogrammed in order to support their rapid proliferation. Elevated fatty acid synthesis is one of the most important aberrations of cancer cell metabolism. An enhancement of fatty acids synthesis is required both for carcinogenesis and cancer cell survival, as inhibition of key lipogenic enzymes slows down the growth of tumor cells and impairs their survival. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
144
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(149 citation statements)
references
References 284 publications
4
144
1
Order By: Relevance
“…IL, interleukin; GM-CSF, granulocyte macrophage colony-stimulating factor; VEGF, vascular endothelial growth factor; VCAM1, vascular cell adhesion molecule 1; SEH, soluble epoxide hydrolase; CYP51A1, cytochrome P450 family 51 subfamily A member 1; Acetyl-CoA, acetyl-coenzyme A; HMG-CoA, 3-hydroxy-3-methylglutaryl-coenzyme A; FPP, farnesyl pyrophosphate; GPP, geranyl pyrophosphate. and its components, including diabetes, obesity and dyslipidemia, have been recognized as modifiable risk factors for pancreatic cancer (72,73). Evidence discussed in the present review has demonstrated that statins potentially reduce pancreatic cancer risk and improve survival in patients with a combination of metabolic syndrome and pancreatic cancer.…”
Section: Discussionmentioning
confidence: 94%
“…IL, interleukin; GM-CSF, granulocyte macrophage colony-stimulating factor; VEGF, vascular endothelial growth factor; VCAM1, vascular cell adhesion molecule 1; SEH, soluble epoxide hydrolase; CYP51A1, cytochrome P450 family 51 subfamily A member 1; Acetyl-CoA, acetyl-coenzyme A; HMG-CoA, 3-hydroxy-3-methylglutaryl-coenzyme A; FPP, farnesyl pyrophosphate; GPP, geranyl pyrophosphate. and its components, including diabetes, obesity and dyslipidemia, have been recognized as modifiable risk factors for pancreatic cancer (72,73). Evidence discussed in the present review has demonstrated that statins potentially reduce pancreatic cancer risk and improve survival in patients with a combination of metabolic syndrome and pancreatic cancer.…”
Section: Discussionmentioning
confidence: 94%
“…Carcinogenesis is associated with substantial changes in cellular metabolism, including alterations of lipid, carbohydrate, nucleic acid and amino acid metabolism [6]. These changes promote rapid proliferation of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have enlighten several metabolic routes and signaling pathways that control tumor progression (36). The most important pathways are considered the following: glutamine regulatory enzymes, Ras signaling, lipid metabolism and autophagy (37)(38)(39). Pancreatic cancer as most cancer types are characterized by a high increase in glucose uptake and metabolism (40) and high glycolytic rates the so called "Warburg effect".…”
Section: Cell Metabolism In Pancreatic Cancermentioning
confidence: 99%
“…Until now there was an increasing interest in glucose metabolism and aerobic glycolysis, however; it is becoming clearly evident that the alteration of lipid metabolism is critical for cancer cell metabolism (55). Enzymes involved in lipogenesis and lipolysis have been found overexpressed in pancreatic cancer, in particular fatty acid synthase (FASN) that catalyses the final steps of fatty acid synthesis and ATP citrate lyase (39). It has been observed that elevated levels of FASN protein in cancer cells and in serum of pancreatic cancer patients are associated with poor prognosis (39).…”
Section: Cell Metabolism In Pancreatic Cancermentioning
confidence: 99%
See 1 more Smart Citation